2017
DOI: 10.15446/acag.v66n3.58238
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient accumulation models in the banana (Musa AAA Simmonds cv Williams) plant under nitrogen doses

Abstract: This research determined the effect of four nitrogen (N) doses on the nutritional behavior of (N), potassium (K), phosphorus (P), calcium (Ca) and magnesium (Mg), respectively, in banana Williams, during five plant development stages and two productive cycles. The treatments were as follows: 1) absolute control, 2) 0 N, 3) 161 kg N ha-1, 4) 321.8 kg N ha-1 and 5) 483 kg N ha-1, respectively. A multivariate approach of the differences among cycles was used to adjust the models and eliminate their individual eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…4). Torres et al (2017) stated that, for the doses 161 and 321.8 kg ha -1 of N, there was low agronomic efficiency, corroborating the low response in the nitrogen application as reflected in the C/N ratio with values oscillating between 6 and 6.4 for the absorption zone (Tab. 3).…”
Section: Carbon-nitrogen Ratio (C/n Ratio)mentioning
confidence: 77%
See 3 more Smart Citations
“…4). Torres et al (2017) stated that, for the doses 161 and 321.8 kg ha -1 of N, there was low agronomic efficiency, corroborating the low response in the nitrogen application as reflected in the C/N ratio with values oscillating between 6 and 6.4 for the absorption zone (Tab. 3).…”
Section: Carbon-nitrogen Ratio (C/n Ratio)mentioning
confidence: 77%
“…3). Moreno and Moral (2008) confirmed that low C/N ratios can be associated with an excess of nitrogen that is lost, a situation that can be associated with the low agronomic efficiency observed by Torres et al (2017).…”
Section: Carbon-nitrogen Ratio (C/n Ratio)mentioning
confidence: 98%
See 2 more Smart Citations
“…Fruits with a high content of sugars and acids adapt easily to the dehydration process (Ochoa, 2016;Cañizares, Bonafine & Laverde, 2007;Torres, Sánchez & Cayón, 2017). Therefore, CMFD-Convective Multi Flash-Drying, is a process that can be applied for the crispy fruits production and is an alternative to the lyophilization process (Zotarelli, Almeida & Borges, 2011).…”
Section: Introductionmentioning
confidence: 99%